2018
DOI: 10.1530/rep-17-0380
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5α-reductase alters pregnane metabolism in the late pregnant mare

Abstract: In the latter half of gestation in the mare, progesterone concentrations decline to near undetectable levels while other 5α-reduced pregnanes are elevated. Of these, 5α-dihydroprogesterone and allopregnanolone have been reported to have important roles in either pregnancy maintenance or fetal quiescence. During this time, the placenta is necessary for pregnane metabolism, with the enzyme 5α-reductase being required for the conversion of progesterone to 5α-dihydroprogesterone. The objectives of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Early studies identified 5a-reduced androstanediols in urine from pregnant mares [62] and B-ring unsaturated androgens [63,64] that to our knowledge have never been quantified in equine blood for instance. Considering the levels of expression and activity of 3bHSD and 5a-reductase in the equine placenta and endometrium [28,37,65], it seems likely that 5a-reduced androgens are more likely candidates to be secreted in relatively high concentrations. Further investigation will be necessary to identify what (if any) sulphated androstanes are secreted during equine gestation, perhaps requiring gas chromatography mass spectrometry as a more powerful discovery tool [20,66].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies identified 5a-reduced androstanediols in urine from pregnant mares [62] and B-ring unsaturated androgens [63,64] that to our knowledge have never been quantified in equine blood for instance. Considering the levels of expression and activity of 3bHSD and 5a-reductase in the equine placenta and endometrium [28,37,65], it seems likely that 5a-reduced androgens are more likely candidates to be secreted in relatively high concentrations. Further investigation will be necessary to identify what (if any) sulphated androstanes are secreted during equine gestation, perhaps requiring gas chromatography mass spectrometry as a more powerful discovery tool [20,66].…”
Section: Discussionmentioning
confidence: 99%
“…Logically, the apparent loss of 5α-reductase activity in the placenta at foaling would be expected to decrease metabolism of progesterone overall. Indeed, inhibition of 5α-reductase activity in the late pregnant mare is associated with an increase in maternal and foetal progesterone concentrations (Wynn et al 2018a). Yet, at term, progesterone reappears in maternal blood (Fig.…”
Section: Steroidogenesis In Late Gestation and At Parturitionmentioning
confidence: 99%
“…pregnant mare (Wynn et al, 2018a) and in foals (Müller et al, 2019). However, our study is the first to perform a complete analysis of PROG metabolites in equine saliva and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…For example, progesterone (PROG) and 17b-estradiol (17b-E2) measurements in plasma of cyclic mares by enzyme immunoassay and radioimmunoassay, respectively, showed that concentrations of PROG begin to increase the day of ovulation, reach maximal concentrations at 6 to 8 days post-ovulation and decrease until day 14 post-ovulation whereas concentrations of 17b-E2 reach a peak 2 days before ovulation and then decrease (Ginther et al, 2005;Aurich, 2011). Gas chromatography coupled to mass spectrometry (GC-MS), liquid chromatography coupled to mass spectrometry (LC-MS) and tandem mass spectrometry (LC-MS/ MS) analysis have been developed to measure some pregnanes (C21-steroids), androstanes (C19-steroids) and estranes (C18steroids) in serum of male and female uncharacterized horses (Genangeli et al, 2017;Dufour et al, 2021) and in plasma throughout equine gestation (Scholtz et al, 2014;Legacki et al, 2016;Wynn et al, 2018a;Ledeck et al, 2022). Analysis in pregnant mares showed that plasmatic PROG concentrations were high during the first 12 weeks of pregnancy and declined progressively until undetectable levels by day 200.…”
Section: Introductionmentioning
confidence: 99%